Recognition of depression and protrusion features on B-rep models based on virtual loops. Issue 1 (2nd January 2016) - Lai, Jiing-Yih; Wang, Ming-Hsuan; Chiu, Yu-Kai; Hsu, Chia-Hsiang; Tsai, Yao-Chen; Huang, Chung-Yi
ABSTRACT: Loops are vital elements in B-rep models and are used to describe the boundary contours of faces. A loop is only defined on a single face, which does not reflect real situations in which features mostly lie across multiple faces. The objective of this study is to detect virtual loops across multiple faces and subsequently use them for recognizing depression and protrusion features in computer-aided design models. Three loop types are defined: single, virtual, and multivirtual loops; virtual and multivirtual loops lie across multiple faces with different boundary conditions across faces. The data of the detected loops are then used to develop a feature recognition algorithm for identifying various depression and protrusion types, ranging from simple circular holes on a face to complex irregular pockets on multiple faces with fillets. This paper provides a detailed description of the proposed algorithm and presents several examples to illustrate its feasibility. GRAPHICAL ABSTRACT: